How does the recurrence of fire affect the regeneration of pine-dominated Mediterranean communities ? - Eugenio M.; Lloret F. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
The post-fire regeneration of Mediterranean communities dominated by Pinus halepensis was examined using a regional approach in Catalonia (NE Iberian Peninsula). The study design comprised 28 study sites conformed by neighboring areas burnt once versus twice along 20 years. In all of them, last fire occurred in 1994. Several surveys have been conducted from year 2002 on: records on vegetation structure (height, cover, Rothermel's fuel models), P. halepensis (density, percentage of trees bearing cones, height), and soil organic horizons (frequency of appearance, dry masses) have been taken and comparatively analyzed in paired once- and twice-burnt areas. Our study reveals that fire recurrence has important cumulative effects on the regeneration of the studied communities. In more recurrently burnt areas, a noticeable structural simplification of vegetation and soil organic horizons has been observed, together with a decline of P. halepensis populations. Both structural and compositional changes seem to be related with an insufficient length of fire intervals.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)